Equilibrium configurations of the interstellar medium layers in the presence of magnetic field and gravitation - V. A. Antonov; O. A. Zheleznyak (Вісник Астрономічної школи, 2003)
Equilibrium configurations of the interstellar medium layer, which is in an external or its own gravitational field and is simultaneously subjected to a force magnetic field was determined. The law of change of the surface density in both cases is identical. The bend of the equilibrium mean line in an external gravitational field follows the sinusoidal law.